Intestinal host defense outcome is dictated by PGE(2) production during efferocytosis of infected cells - Dejani, Naiara Naiana [UNESP]; Orlando, Allan Botinhon [UNESP]; Nino, Victoria Eugenia [UNESP]; Penteado, Leticia de Aquino [UNESP]; Verdan, Felipe Fortino [UNESP]; Ribeiro Bazzano, Julia Miranda [UNESP]; Codo, Ana Campos [UNESP]; Guerta Salina, Ana Carolina [UNESP]; Saraiva, Amanda Correia [UNESP]; Avelar, Matheus Rossi [UNESP]; Spolidorio, Luis Carlos [UNESP]; Serezani, C. Henrique; et al. (Natl Acad Sciences, 2018)
Inflammatory responses are terminated by the clearance of dead cells, a process termed efferocytosis. A consequence of efferocytosis is the synthesis of the antiinflammatory mediators TGF-beta, PGE(2), and IL-10; however, the efferocytosis of infected cells favors Th17 responses by eliciting the synthesis of TGF-beta, IL-6, and IL-23. Recently, we showed that the efferocytosis of apoptotic Escherichia coli-infected macrophages by dendritic cells triggers PGE(2) production in addition to pro-Th17 cytokine expression. We therefore examined the role of PGE(2) during Th17 differentiation and intestinal pathology. The efferocytosis of apoptotic E. coli-infected cells by dendritic cells promoted high levels of PGE(2), which impaired IL-1R expression via the EP4-PKA pathway in T cells and consequently inhibited Th17 differentiation. The outcome of murine intestinal Citrobacter rodentium infection was dependent on the EP4 receptor. Infected mice treated with EP4 antagonist showed enhanced intestinal defense against C. rodentium compared with infected mice treated with vehicle control. Those results suggest that EP4 signaling during infectious colitis could be targeted as a way to enhance Th17 immunity and host defense.
Keywords: efferocytosis; infected apoptotic cells; prostaglandin E-2; Th17 cells; EP4